Comparison of CTDIw and Homogeneity Index on CTDI Phantoms - Utami, Moh. Shofi Nur; Asni, Nur; Haryanto, Freddy; Laksono, Muharam Budi; Yusifa, Anggun; Nermina, Nermina (Universitas Negeri Semarang, 2023)
The study was conducted to compare the Computed Tomography Dose Index Weighted (CTDIw) value values and homogeneity index on head and body phantoms with tube voltage variations. Two CTDI phantoms are Gammex (Sun Nuclear, Florida, United States) and IBA (IBA Dosimetry, Schwarzenbruck, Germany). The pencil ionization chamber was used for the measurement of CTDI. The measurements were carried out with a Toshiba Alexion 16 MSCT in a single rotation of axial mode with detector position in the phantom’s center, top, bottom, right, and left. Tube voltage values are 80 kVp, 100 kVp, and 120 kVp. Then, the homogeneity test of the phantom was carried out. The homogeneity value was obtained by measuring the average CT number in the image by determining the region of interest (ROI) at positions namely a, b, c, d, and e, In addition the ratio of the two phantoms was also carried out. The ratio was obtained from the difference of the CTDI100 value at the edge to the CTDI100 value at the center of the head and body phantom from Gammex and IBA. The results showed that the CTDIwof the Gammex head phantom are 26.83 mGy (80 kV), 53.32 mGy (100 kV) and 83.32 mGy (120 kV). While the CTDIw of the Gammex body phantom are 11.73 mGy (80 kV), 21.58 mGy (100 kV) and 36.45 mGy (120 kV). In comparison, CTDIw of the IBA head phantom are 27.01 mGy (80 kV), 55.33 mGy (100 kV) and 81.69 mGy (120 kV). While the CTDIw of the IBA body phantom are 11.85 mGy (80 kV), 23.32 mGy (100 kV) and 35.00 mGy (120 kV). The differences in CTDIw of the two phantoms were within (head phantom is 0.18 % – 2.01 %) and (body phantom is 0.13 % – 1.75 %). The difference below 5% with the p-value of the head phantom is 0.87 and body phantom is 0.89 (more than 0.05) indicates that the two phantoms are not significantly different because the two phantoms are made of the same material. The average ratio for the Gammex head phantom is 1.12 – 1.28, while the IBA head phantom is 1.07 – 1.28. Then the average ratio for the Gammex body phantom is 2.03 – 2.56, while for the IBA body phantom is 1.91 – 2.59 which indicates that the head phantom produces a more uniform dose distribution compared to a body phantom. The average homogeneity value of the IBA phantom is 90.52 % and the average homogeneity value of the Gammex phantom is 87.15 % (a difference of around 3.37%). This value shows that Gammex and IBA phantom have fairly good homogeneity